Model of information protection process - Браиловский, Н. Н.; Хорошко, А. В.; Хорошко, В. А.; Чирков, Д. В. (Proceedings of National Aviation University (archive), 1999)
Designed is the model of information protection process which allows to evaluate the effectiveness of technical protection system